PEMAHAMAN KONSEP GEOMETRI GARIS LURUS PADA MAHASISWA BARU PENERIMA BEASISWA KIP KULIAH - Nurhakim, Lukman; Bistari, Bistari; Yani, Ahmad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
The students frequently have trouble in learning geometry because of a lack of conceptual understanding of the elements and properties of learning geometry. Therefore, we need the presence of early analysis to know the difficulties that were felt by students. The research is qualitative research to describe the conceptual understanding of geometry lines of new students who get the scholarship KIP Kuliah. Subjek of Research taken from three students has high, middle, and low cognitive ability, based on the school report card. The research results are 33% of new students who get the scholarship KIP kuliah cannot repeat the said formula learned, 33% can present geometry concept lines on other from, 66% cannot determine the mandatory terms and the compulsory minimum from a concept and all of the students who get the scholarship KIP kuliah cannot implement and choice concept for finish mathematic problems.